2016
DOI: 10.1177/0149206315618012
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Reasoning Test for Creative Personality: Rationale, Theoretical Development, and Validation

Abstract: The innovations of creative individuals are regarded as vital for business functioning and survival. To this end, efforts have been made to design measures of creative personality in hopes of predicting creative performance. Current measures of creative personality all reside at the explicit level, yet theory and research both suggest that a large proportion of personality can also be conceptualized at the implicit level. We address this issue by presenting a theoretical basis for creative personality that ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 85 publications
(173 reference statements)
3
51
0
2
Order By: Relevance
“…As we argued before, different types of implicit measures are most likely complementary and not interchangeable, tapping into different mechanisms and relating to different outcomes. Schoen and colleagues [ 59 ], for example, recently developed a CRT measure to assess a person’s implicit creative personality and found that it is a substantial predictor of creative performance. Yet, other implicit measures of creative personality, such as a BIAT, an OMT or a I-PSQ-type of questionnaire, could most likely add to the knowledge of creative personality and performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we argued before, different types of implicit measures are most likely complementary and not interchangeable, tapping into different mechanisms and relating to different outcomes. Schoen and colleagues [ 59 ], for example, recently developed a CRT measure to assess a person’s implicit creative personality and found that it is a substantial predictor of creative performance. Yet, other implicit measures of creative personality, such as a BIAT, an OMT or a I-PSQ-type of questionnaire, could most likely add to the knowledge of creative personality and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pattern of selected solutions is indicative of the justification mechanisms that people apply, and hence of the underlying unconscious or implicit processes through which people motivate their behaviors and thoughts. CRTs have been successfully developed and used for the assessment of achievement motivation [ 13 ], aggression [ 57 ], power [ 58 ], creativity [ 59 ], addiction proneness [ 60 ], and most likely also for a number of other constructs. Recent studies, including two meta-analyses, show that the CRT has good psychometric qualities [ 60 63 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditional reasoning test was initially developed to measure implicit aspects of achievement motivation (James, 1998), and aggressiveness (James et al, 2005), but today it is used to measure certain aspects of leadership (James et al, 2013), team orientation (O'Shea et al, 2004), delays, absenteeism and withdrawal (Nieminen, 2012), addiction tendencies (Bowler and Bowler, 2014), and creativity (Schoen et al, 2016).…”
Section: Conditional Reasoning Tests (Crt)mentioning
confidence: 99%
“…3 Individual differences do exist. Even though employees with creative potential can think outside the box (Amabile & Pratt, 2016) and are willing to take risk (Schoen et al, 2016), it is conceivable that some individuals may not feel comfortable with the particular type of risk associated with handling rules. Similarly, some individuals may not feel that this is the "right" thing to do (March & Olsen, 2011).…”
Section: Individual Positionmentioning
confidence: 99%